The New Encyclopedia of Science : Evolution and Genetics : The Molecules of Inheritance - Bailey, Jill; Advisory Editor D'Argenio, David Dr. and Ridley, Mark Dr. (New York Oxford University Press, 2003)
A color-illustrated encyclopedia of evolution and genetics containing short definitions to approximately four hundred terms, cross-referenced to more than forty thematic spreads. Also includes knowledge maps and a time line.
Include Color Illustration and Index
Keywords: Molecular evolution -- Genetics